(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Understanding clinical characteristics of patient is important to plan human resource and logistics. Moreover, this gives understanding of pattern of disease. This study aim to find the clinical characteristics observed in patients with suspected COVID-19 admitted at Patan Hospital. Method: This is cross sectional descriptive study conducted at Patan Hospital, Patan Academy of Health Sciences, Nepal, on April 2020. Suspected COVID-19 patient admitted from January 25 to April 20, 2020 is taken for the study. Record files were retrieved from record section and patient’s age, gender, place of residence, travel history, duration of symptom onset, symptoms on admission like fever, cough, rhinorrnoea, sore throat, myalgia and shortness of breath was recorded. Signs on admission like temperature, pulse, blood pressure, respiratory rate and oxygen saturation were also recorded. Data were descriptive analyzed. Ethical approval was obtained. Result: Total 40 suspected COVID-19 patients got admitted from 25 January to 20 April 2020. Of these admissions 25 (62.5%) were male, median age was 30 years, median days of return from abroad was 9 days, average duration of stay at hospital was 3.8 days. There were two COVID-19 positive patients who were asymptomatic. Conclusion: Travel history and history of travel to the community inside the country where COVID-19 has been detected is important to suspect COVID-19.